A Portuguese perspective on continuous training in ICT in Portugal : essential or mere accreditation? - Sampaio, Patrícia Alexandra da Silva Ribeiro (2011)
This paper presents a research study conducted with two groups of teachers from different schools and curricular subject areas within the context of the official continuous training program in a workshop context on interactive whiteboards. A questionnaire evaluating ICT literacy, as well as the satisfaction level of teachers regarding the type of training program they had attended was driven at the end of the training program. After nine months of its implementation, half the teachers were contacted again to conduct another survey on the applicability of the training program they had attended in order to know/understand the possible changes in their teaching practices. The goal of the study was to investigate the influence of training in ICT in changing the teaching practices of in service teachers of primary and secondary education, analyzing the effectiveness of the program in the integration of technologies as learning tools in the classroom. This study aims at an improvement of the practices adopted by trainers and the search for effective training models implemented in the continuous education of teachers.